2002
DOI: 10.1159/000070423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenprocoumon on Monitoring of Lepirudin, Argatroban, Melagatran and Unfractionated Heparin with the PiCT Method

Abstract: Prothrombinase-induced clotting time (PiCT) is a clotting-time test for heparins and direct thrombin inhibitors to reduce drawbacks of aPTT. Effects of the direct thrombin inhibitors lepirudin, argatroban, melagatran and of unfractionated heparin (UFH) were investigated in normal and oral anticoagulant plasma samples. Lepirudin showed potentiating interferences with phenprocoumon effects. Melagatran, argatroban and UFH delivered distinct linear additive effects in both plasma sample groups. PiCT ratio reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…34 The effect of warfarin on the PiCT was examined previously by Fenyvesi et al 33 Warfarin pretreatment had only a minor effect on the monitoring of UFH using PiCT. In contrast, prothrombin inhibition by recombinant hirudin or other substances led to considerably prolonged clotting times in warfarin-pretreated subjects compared with "normal" subjects.…”
Section: Evaluation Of Assay Components Of Pictmentioning
confidence: 97%
See 2 more Smart Citations
“…34 The effect of warfarin on the PiCT was examined previously by Fenyvesi et al 33 Warfarin pretreatment had only a minor effect on the monitoring of UFH using PiCT. In contrast, prothrombin inhibition by recombinant hirudin or other substances led to considerably prolonged clotting times in warfarin-pretreated subjects compared with "normal" subjects.…”
Section: Evaluation Of Assay Components Of Pictmentioning
confidence: 97%
“…33 Recently, it was also shown that PiCT may be used for newer compounds such as sulfaminoheparosans 39 and direct FXa inhibitors. 34 For the latter, however, it may be advantageous to perform PiCT …”
Section: Analysis Of R-hirudin Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The activated partial thromoplastin time (aPTT) is an accepted coagulation parameter suitable to monitor argatroban in most other clinical applications with the lower doses 6 , 11 . However, the ecarin time (ECA‐T) is a more specific monitoring parameter for DTIs, although it is not yet standardized for routine clinical practice 11 , 12 . The prothrombinase‐induced clotting time (PiCT) is also prolonged by argatroban and has been suggested as an alternative coagulation parameter to monitor argatroban therapy 12 .…”
mentioning
confidence: 99%
“…They are easy bioavailable, and they have longer plasma half-life and a more predictable anticoagulant response. Furthermore, they have less adverse after- for monitoring all anticoagulants 3,4 and to reduce the flaws of aPTT [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%